2019
DOI: 10.1101/847343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Transcriptome and Promoter Architecture of the African Swine Fever Virus

Abstract: The African Swine Fever Virus causes haemorrhagic fever in domestic pigs and presents the biggest global threat to animal farming in recorded history. Despite its importance, very little is known the mechanisms and temporal regulation of transcription in ASFV. Here we report the first detailed viral transcriptome analysis of ASFV during early and late infection of Vero cells. In addition to total RNA sequencing, we have characterised the transcription start sites and transcription termination sites at nucleoti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The recombination plasmid p72mCherryΔI177L was designed according to the original sequence of ASFV Georgia/2007 (3). To further add complexity to the I177L gene, a recent preprint (29) analyzing the transcriptome of ASFV, only the shortened version of I177L, as originally annotated (3), was detected as a late protein transcript, while the full-length transcript of I177L was not detected. We suggest reannotation of the I177L gene to the shortened ORF.…”
Section: Discussionmentioning
confidence: 99%
“…The recombination plasmid p72mCherryΔI177L was designed according to the original sequence of ASFV Georgia/2007 (3). To further add complexity to the I177L gene, a recent preprint (29) analyzing the transcriptome of ASFV, only the shortened version of I177L, as originally annotated (3), was detected as a late protein transcript, while the full-length transcript of I177L was not detected. We suggest reannotation of the I177L gene to the shortened ORF.…”
Section: Discussionmentioning
confidence: 99%
“…ASFV transcription termination takes place at a conserved motif of seven or more consecutive thymidylate residues ( 57 ), and this poly(T) motif is retained in the mRNA ( 58 ), so it is possible this poly(U) motif is the termination signal for ASFVsRNA2 transcription. Recent detailed viral transcriptome analysis of ASFV has indicated that this motif is the termination sequence for the gene upstream of C475L, C135R ( 59 ). Therefore, it is possible ASFVsRNA2 is generated through modification of the C135R mRNA transcript or as a result of readthrough transcription of this transcript.…”
Section: Discussionmentioning
confidence: 99%